Blood in breastmilk: Safety issues and Islamic ruling - Jamani, Nurjasmine Aida; Mohamad, Hasbullah (2016)
Blood in breastmilk is not an uncommon encounter for nursing mothers. It can raise anxiety and concern from medical health and Islamic perspectives to Moslem mothers whether it is safe to consume. We report a case of blood stained breastmilk in a nursing mother, its safety and Islamic ruling dilemma and the need to reinforce breastfeeding. A 25-year woman, Para 1 complained of blood -tinged breastmilk while expressing her breastmilk via mechanical breastpump from her right breast at her workplace for one- day duration. She has no known medical illness. Her child was a 6-month old infant who breastfed exclusively since birth. She also complained of painful nipple on the right breast. However, there was no other associated symptoms such as nipple discharge, breast mass or fever. Clinical examination showed normal vital signs. Breast examination showed that there is a small crack over the right nipple which is tender to touch. No active bleeding, swelling, redness, mass, abrasion or nipple discharge was noted. A gradual lightening of the blood- tinged milk to white colour was noted in few days. Breastfeeding was advised to be continued. Discussion on the safety of the bloodstained breastmilk from medical aspects and Islamic ruling of the stand point of legal theorists (usul al-fiqh) and legal maxim (qawai’idfiqhiyyah) will be further deliberated. This case highlights the uncommon problem but importantin Moslem nursing mothers in terms of safety from medical and Islamic ruling perspectives.